Perspective on management of Transient Ischemic Attack in the emergency department - Das, Sunil Kumar; Sah, Sunny; Chaudhary, Shardananda; Luitel, Aayash; Gurung, Raju (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Transient ischemic attack (TIA) is commonly presented at the emergency department as transient and nonspecific symptoms, which are difficult to localize and interpret. It is often required to have strong clinical suspicion to diagnose TIA. Optimal blood pressure control is of utmost importance to minimize hazardous consequences of TIA and stroke. There have been many scoring systems to predict stroke after TIA but none of them are reliable to access low or high risk for early recurrent stroke. There is emerging evidence among association between high D-Dimer level and acute ischemic stroke followed by TIA but a dose-dependent relationship between D-Dimer and the risk of stroke is yet to be established. Until now neuroimaging has been the investigation of choice for detecting TIA and stroke.